Combining Biocontrol Agent With Plant Nutrients for Integrated Control of Tomato Early Blight Through the Modulation of Physio-Chemical Attributes and Key Antioxidants - Awan, Zoia Arshad; Shoaib, Amna; Iftikhar, Muhammad Sarmad; Jan, Basit Latief; Ahmad, Parvaiz (Frontiers in Microbiology, 2022)
Early blight (EB) is one of the major fungal diseases caused by Alternaria solani responsible for destructive tomato production around the globe. Biocontrol agent/s can be adequately implemented in an integrated management framework by using it in combination with vital plant nutrients e.g. nitrogen, phosphorus, potassium (NPK) and zinc (Zn). The current study was aimed to assess the integrated effect of a biocontrol agent Bacillus subtilis (BS-01) and the selective plant nutrients (NPK and Zn) on EB disease management and tomato crop performance. A field experiment was conducted for the off-season tomato production (under-walk-in tunnels) in Punjab, Pakistan. The trial was set in a randomized complete block design (RCBD) and comprised of 9 treatments of a biocontrol agent (BS-01) either alone or in combination with the plant nutrients viz., NPK (64:46:50 kg acre-1) & Zn (10 kg acre-1) as sustainable disease managing approach against EB. In addition, the biocontrol efficacy of B. subtilis (BS-01) on a fungal load of A. solani was estimated by quantitative PCR assays, where the foliar application of BS-01 on tomato plants either alone or in combination with the plant nutrients was done as a preventive measure. Our results revealed that the interactive effect of BS-01 with plant nutrients conferred significantly a varying degree of resilience in the infected tomato plants against EB by effectively modifying the content of total chlorophyll, carotenoids & total phenolics along with the activities of antioxidant enzymes (SOD, CAT, POX, PPO and PAL). Also, the integrative effect of BS-01 and plant nutrients proved significantly effective in reducing pathogen load on inoculated tomato foliage, displaying the desired level of protection against A. solani infection. Besides, the complementary interaction of BS-01+Zn+NPK worked synergistically to improve crop productivity by providing the highest marketable yield (21.61 tons acre-1) and net profit (3,61,363 PKRs acre-1). This integrated approach is put forward as a way to reduce the fungicide doses to control EB that would act as a sustainable plant protection strategy to generate profitable tomato production.